Prognostic factors in childhood-acquired brain injury. (16th April 2018) - Shaklai, Sharon; Peretz Fish, Relly; Simantov, M; Groswasser, Z
ABSTRACT: Background : A long-term follow-up study comparing children after anoxic brain injury (AnBI) with those after traumatic brain injury (TBI) was conducted, and prognostic factors were mapped. Methods : A prospective historical study following long-term functional outcome after childhood brain injury was conducted in two phases. The first phase included patients suffering from moderate-severe TBI. The second phase assessed children after AnBI, and the results were compared. Functional outcome was recorded and factors influencing prognosis were outlined. Results : On admission vegetative state (VS) was twice as prevalent in the AnBI subgroup. Approximately 90% of children with TBI and 60% of patients with AnBI gained independency in activities of daily living (ADL) and mobility. Long-term positive outcome, i.e., return to school and open-market employment, were higher in patients with TBI when compared with AnBI (61% and 48.1%, respectively). Significant outcome-predicting factors were VS at admission to rehabilitation, length of loss of consciousness (LOC) up to 11 days and functional independence measure (FIM) score at admission and discharge. Aetiology was not found to be a predicting factor. Conclusions : Duration of unconsciousness is the main long-term negative prognostic outcome factor. Anoxic brain damage, associated with longer periods of unconsciousness also heralds a less favourable outcome.